On the shape and evolution of a cosmic-ray-regulated galaxy-wide stellar initial mass function - Fontanot, Fabio; Pasquali, Anna (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. In this paper, we present a new derivation of the shape and evolution of the integrated galaxy-wide initial mass function (IGIMF), incorporating expl